Driving Factors Of Intellectual Capital In A Literature Review - Kasir, Kasir (Journal of Accounting Inaba, 2025)
This research is in the form of a literature review in the field of financial accounting which aims to determine what factors are influenced by intellectual capital and how the research results are. This research employs a qualitative method utilizing a literature approach via a literature review. Where the articles studied were 43 articles sourced from emerald.com, elseiver.com, springer.com, googleschoolar.com and other websites by filtering research titles and using the keyword "Intellectual Capital" from 2019 to 2023. The results of the study indicate that intellectual capital and its components have a positive and significant influence on financial and company performance/efficiency, in addition to company innovation, financial reporting, entrepreneurial interest and technology and a small part on other factors such as competitiveness, informal economy, cost audits, strategic alliances, management control systems, business strategies, corporate governance, knowledge generation equity capital costs and scientific papers. And for further studies the author suggests factors that influence intellectual capital which are equipped with country studies.